2010
DOI: 10.1097/jom.0b013e3181e48ec8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between IL-1A Single Nucleotide Polymorphisms and Chronic Beryllium Disease and Beryllium Sensitization

Abstract: These results indicate that genetic variations in the IL-1A gene may play a role in the development of CBD but not BeS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…On the other hand, Dotti et al, reported that the TNFa -308A and -857T variants are significantly associated with BeS (Dotti et al, 2004). McCanlies et al, showed that IL-1a-1142, -3769, and -4697 variants were significantly associated with CBD compared to individuals with BeS or nonsensitized workers after adjusting for Glu69 status (McCanlies et al, 2010). These results suggested that the formation of granulomas in CBD may require an independent inflammatory response controlled by genes unrelated to Be recognition.…”
Section: Chronic Beryllium Diseasementioning
confidence: 85%
See 1 more Smart Citation
“…On the other hand, Dotti et al, reported that the TNFa -308A and -857T variants are significantly associated with BeS (Dotti et al, 2004). McCanlies et al, showed that IL-1a-1142, -3769, and -4697 variants were significantly associated with CBD compared to individuals with BeS or nonsensitized workers after adjusting for Glu69 status (McCanlies et al, 2010). These results suggested that the formation of granulomas in CBD may require an independent inflammatory response controlled by genes unrelated to Be recognition.…”
Section: Chronic Beryllium Diseasementioning
confidence: 85%
“…The -509C and codon 10T variants of the transforming growth factorebeta1 (TGFb) gene, a cytokine which helps control the fibrotic/Th1 response, were found to be associated with more severe granulomatous disease in CBD (Jonth et al, 2007). While Saltini et al reported an association between the TNFa-308*02 variant and BeS and CBD, this result was not confirmed in a large population-based study (Saltini et al, 2001;McCanlies et al, 2007). On the other hand, Dotti et al, reported that the TNFa -308A and -857T variants are significantly associated with BeS (Dotti et al, 2004).…”
Section: Chronic Beryllium Diseasementioning
confidence: 87%
“…While Saltini et al reported an association between the TNF α -308*02 variant and BeS and CBD, this result was not confirmed in a large population-based study [57, 68]. A recent study showed that IL-1 α -1142, -3769, and -4697 variants were significantly associated with CBD compared to individuals with BeS or nonsensitized workers after adjusting for Glu69 status [69]. These results suggested that the formation of granulomas in CBD may require an independent inflammatory response controlled by genes unrelated to beryllium recognition.…”
Section: Chronic Beryllium Diseasementioning
confidence: 99%
“…The use of genetic information, along with all of the other factors that contribute to occupational morbidity and mortality, will play an increasing role in preventing occupational disease. However, the use of genetic information in occupational safety and health research and practice presents both promise and concerns [McCanlies et al 2003;Kelada et al 2003;Henry et al 2002;Christiani et al 2001;Schulte et al 1999]. Use of genetic information raises medical, ethical, legal and social issues [Clayton 2003;Ward et al, 2002;McCunney 2002;Christiani et al 2001;Rothstein 2000a;Schulte et al 1999;Lemmens 1997;Barrett et al 1997, Van Damme et al 1995Gochfeld 1998;Omenn 1982].…”
Section: Executive Summarymentioning
confidence: 99%
“…The trend in research today is to evaluate multiple genes in a study rather than assess the role of single genes. In addition to carcinogenesis, there has been substantial focus on respiratory diseases and allergic responses [McCanlies et al 2003;Kalsheker and Morgan 1990;Brain et al 1988;Rystedt 1985;Chan-Yeung et al 1978]. Beyond that, studies on the gene-occupational environment interaction for such conditions as diabetes, myocardial infarction, and immune function defects have been documented [Omori et al 2002;Nakayama et al 2002;Oizumi et al 2001;Spiridonova et al 2001;Altshuler et al 2000;Keavney et al 2000;Fujisawa et al 1996;Walston et al 1995].…”
Section: Gene-environment Interactions In Occupational Safety and Hea...mentioning
confidence: 99%